3D‐Printing Strong High‐Resolution Antioxidant Bioresorbable Vascular Stents. Issue 9 (7th October 2016) - van Lith, Robert; Baker, Evan; Ware, Henry; Yang, Jian; Farsheed, Adam Cyrus; Sun, Cheng; Ameer, Guillermo
Abstract : 3D‐printed stents are fabricated with high speed and resolution by micro‐continuous liquid interface production (microCLIP) of a bioresorbable, antioxidant, photopolymerizable polydiolcitrate biomaterial. Printed stents can match the mechanical properties of bare metal stents and strengthen porcine arteries after deployment. This technology is a big step forward toward on‐the‐spot and on‐demand printing of patient‐specific stents.